Fiscal and Financial Balance Victoria Hospital ESE 2014-2017 (2014)
Search the financial viability of ESE Victoria Hospital, through the implementation of the program of fiscal and financial restructuring with the application of administrative measures and seeking to contain health care spending and increase revenue.